Expression of microRNAs-21 and-223 in hepatocellular carcinoma in hepatitis C virus infected Egyptian population - Eman A. Elghoroury, Soheir A. Abdel Maksoud, Dina Kandil, Mona Raafat El Kafoury, Eman Mahmoud Hassan, Eman Awadallah, Mohamed A. Hussein, Hany Ahmed Elghobary (Journal of Applied Pharmaceutical Science, 2017)
Background: The prognosis of hepatocellular carcinoma (HCC) in Egypt is poor due to high prevalence of hepatitis C virus (HCV). Moreover, the performance of laboratory markers for diagnosis of HCC at early stages has not been optimal.
Keywords: CAP2,HCV,HCC,MIF,microRNAs.